Penerapan Sistem Informasi Tracer Study Pada Universitas Muhammadiyah Kotabumi - Muhammad Adie Syaputra; Irma Fatima (LPPM Universitas Muhammadiyah Kotabumi, 2020)
Tracer Study is research on the situation of alumni that aims to get a lot of information from graduates / alumni to improve the quality of graduates. Tracking alumni information that can be used as input and evaluation for improving learning and the competencies of graduates. Information in the form of activities / activities of the graduates / alumni after taking education at UMKO, both in the waiting period or having activities in the work world. Computerized tracer studies online in tracking alumni can easily list the desired alumni that can be directly provided by graduates / alumni, where the system built can record graduates / alumni based on graduation years, cometensi fields, number of graduates, job profiles depicted in the form percentage, graph or diagram. Software development uses OOSE method with stages: (1) Requirement Engineering, (2) Object Oriented Design, (3) Implementation or Coding, (4) Testin. The tracking process using an integrated system is able to connect and store all graduate information in 1 (one) media, so that it can provide information to anyone who needs it. In addition, the data entered directly by the alumni so that the data level is more accurate, so that it can provide input to UMKO to improve the quality of graduates.